Overview Ekonomi Makro Islam - Farkhatul Hayati; Amanda Luqianna; Mutiara Oktavina; Muhammad Taufiq Abadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
Islamic economics is an economic framework based on the principles of Islamic teachings, combining religious values with sustainable and just economic concepts. This journal explores the scope of Islamic economics by focusing on the core principles that form the basis of the economic system. Apart from that, there is also the impact of Islamic economics in building financial inclusion and fighting economic inequality. By upholding the values of justice and social responsibility, Islamic economics encourages financial inclusion by providing access to financial services to disadvantaged groups in society. This approach helps reduce disparities between different economic groups and creates broader opportunities for sustainability and equitable economic development. However, although Islamic economics offers a useful approach, this article also discusses the challenges faced by Islamic economic practices in dealing with the complexit of the global economy and achieving a balance between finance and religious values. This journal provides a comprehensive overview of the diversity and complexity within the scope of Islamic economics, exploring the implications and opportunities for further development in an ever-evolving global context. This study used descriptive qualitative method. The types of data used are secondary data and primary data